BL_GERICHTE 715 18 46/166 vom 19. Oktober 2017 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht, vom 28. Juni 2018 (715 18 46/166) - BL Gerichte (2017)
Insolvenzentschädigung